Prediction of longitudinal shear resistance of steel-concrete composite slabs. (15th August 2019) - Ahmed, Saddam M.; Avudaiappan, Siva; Sheet, Ikhlas S.; Saavedra Flores, Erick I.; Pina, Juan C.; Yanez, Sergio J.; Guzmán, Carlos F.
Highlights: Longitudinal shear resistance is predicted in steel-concrete composite slabs. Four-point-bending tests are carried out to study shear bond behaviour. Different shear spans on the bond strength and load carrying capacity are examined. A new simplification for m-k curves is proposed. Abstract: In this study, steel-concrete composite slabs are subjected to symmetrical double line loads, and the prediction of longitudinal shear resistance capacity is evaluated using the shear bond mechanism or m-k procedure. The current study uses the experimental testing data with a sufficient shear span distance to predict the effect of the normal force at the interface between the steel plates and concrete which is normally insignificant. All the flexural tested specimens are carried out with the same profiled rib details and the longitudinal shear resistance of composite slabs is measured and compared. Experimental results showed over-estimation of the longitudinal shear resistance because of the frictional force between the profiled steel sheet and the concrete. However, it increases according to the increase of the normal force at the interface between the steel plate and concrete core. The response of different shear spans on the bond strength and load carrying capacity is examined in both elastic and plastic stages. Based on the experimental measurements, we propose a new simplification for m-k curves, called 'λ-q'. This simplification (λ-q) can be used as a guideline to develop new formula taking into account other parameters, such as, embossments, shears connector, slips and shape factor.